Agroindústria alimentar: epicentro do agronegócio no Estado do Ceará (Brasil) - Denise Elias (Confins)
This paper approaches three different theses. First, food agroindustry is of central importance for understanding agribusiness diffusion in Ceará (Brazil). Second, general conditions for capital reproduction of that agribusiness also take place in the Metropolitan Area of Fortaleza, especially in the core municipality. Third, large food agribusiness companies do a corporate use of land in Ceará and thus they figure prominently responsible for important economic and spatial processes. In this way, we basically intend to present an argumentative essay for verification of the three mentioned theses, along three different main sections of this paper. The first section introduces Ceará’s agribusiness profile by size, relating farming settlements and their formal jobs. The second, their spatial distribution over Ceará. And the third section relates food agribusiness and economic activity groups, highlighting large companies as well as economic and spatial processes ignited by them.